Management of Infective Endocarditis in People Who Inject Drugs: A Scientific Statement From the American Heart Association. Issue 14 (31st August 2022) - Baddour, Larry M.; Weimer, Melissa B.; Wurcel, Alysse G.; McElhinney, Doff B.; Marks, Laura R.; Fanucchi, Laura C.; Esquer Garrigos, Zerelda; Pettersson, Gosta B.; DeSimone, Daniel C.
Abstract : Background: The American Heart Association has sponsored both guidelines and scientific statements that address the diagnosis, management, and prevention of infective endocarditis. As a result of the unprecedented and increasing incidence of infective endocarditis cases among people who inject drugs, the American Heart Association sponsored this original scientific statement. It provides a more in-depth focus on the management of infective endocarditis among this unique population than what has been provided in prior American Heart Association infective endocarditis–related documents. Methods: A writing group was named and consisted of recognized experts in the fields of infectious diseases, cardiology, addiction medicine, and cardiovascular surgery in October 2021. A literature search was conducted in Embase on November 19, 2021, and multiple terms were used, with 1345 English-language articles identified after removal of duplicates. Conclusions: Management of infective endocarditis in people who inject drugs is complex and requires a unique approach in all aspects of care. Clinicians must appreciate that it requires involvement of a variety of specialists and that consultation by addiction-trained clinicians is as important as that of more traditional members of the endocarditis team to improve infective endocarditis outcomes. Preventive measures are critical in people who inject drugs and are cured of an initial bout of infective endocarditis because they remain at extremely high risk for subsequent bouts of infective endocarditis, regardless of whether injection drug use is continued.